Transport study of palladium through a bulk liquid membrane using hexadecylpyridinium as carrier - Alizadeh, Naader; Salimi, Shabnam; Jabbari, Ali (Separation and purification technology, 2002)
Hexadecylpyridinium bromide (HDPB) was used as an excellent carrier for the uphill transport of palladium(II) as PdBr 4 2− complex anion through a chloroform bulk liquid membrane. The transport efficiency of palladium(II) by HDPB was investigated under various experimental conditions such as pH and concentration of NaBr in source phase, concentration of surfactant (HDPB) in membrane, HBr and thiourea (as stripping agent) concentration in receiving phase and equilibrium time. In the optimum conditions, transport efficiency of palladium(II) for the ten replicate measurements after 110 min was 97.9±1.1%. The selectivity of palladium(II) transport from aqueous solutions containing Sr 2+, Ca 2+, Ba 2+, Co 2+, Ni 2+, Zn 2+, Cu 2+, Cd 2+, Mn 2+ and Hg 2+ ions was investigated and found that none of cations used, interfere the palladium(II) transport (at M n+/Pd 2+ mole ratio of 10).The proposed method has been applied to separation of palladium in Silicon–Alumina catalysts. The transport efficiency after 120 min was 98%.